2021
DOI: 10.3390/nu13061829
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Circulating Levels of Vitamin D before and after Weight Loss Induced by a Very Low-Calorie Ketogenic Diet

Abstract: Background: Vitamin D plays a pivotal role in calcium and phosphorus metabolism, also influencing bone tissue. Several studies have reported that vitamin D blood levels were significantly lower in people with obesity, probably due to its uptake by the adipose tissue. Clinical studies that investigated the changes of circulating levels of vitamin D following weight loss reported controversial data. A very low-calorie ketogenic diet is acknowledged as a reliable treatment to achieve a rapid weight loss. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 26 publications
3
24
1
1
Order By: Relevance
“…In their study, they evaluated the change in vitamin D concentrations in 31 subjects with obesity before and after dietary treatment with VLCKD. Subjects with obesity had lower vitamin D levels, and at the end of the 10-12 weeks dietary intervention, the increase in vitamin D levels correlated with the reduction in body weight and especially fat mass [44]. Thus, this study supports the hypothesis that vitamin D is stored in adipose tissue and released after weight loss.…”
Section: Pcos and Vlckdsupporting
confidence: 78%
See 1 more Smart Citation
“…In their study, they evaluated the change in vitamin D concentrations in 31 subjects with obesity before and after dietary treatment with VLCKD. Subjects with obesity had lower vitamin D levels, and at the end of the 10-12 weeks dietary intervention, the increase in vitamin D levels correlated with the reduction in body weight and especially fat mass [44]. Thus, this study supports the hypothesis that vitamin D is stored in adipose tissue and released after weight loss.…”
Section: Pcos and Vlckdsupporting
confidence: 78%
“…Hence, weight loss and decreased fat mass might restore regular vitamin D levels and insulin sensitivity. As reported by Buscemi et al, vitamin D blood levels were significantly lower in subjects with obesity, probably due to its uptake by the adipose tissue [44]. In their study, they evaluated the change in vitamin D concentrations in 31 subjects with obesity before and after dietary treatment with VLCKD.…”
Section: Pcos and Vlckdmentioning
confidence: 84%
“…One possible explanation is that the stored 25(OH)D in adipose tissue, especially in visceral fat, was being released following the fat mass reduction. In agreement with our result, Buscemi S, et al also found that significant decrease in BMI, WC and fat mass (FM) induced by a very low-calorie ketogenic diet resulted in the increased serum 25(OH)D levels [ 40 ]. A meta-analysis which recruited 18 clinical trials also demonstrated that serum vitamin D levels were increased with weight and FM loss [ 41 ], further supporting the hypothesis that increases in serum 25(OH)D levels would be a result from direct mobilization of stores into the circulation upon decrease of FM in the obese subjects.…”
Section: Discussionsupporting
confidence: 93%
“…Obesity showed lower concentrations of VD levels, which normalized after weight loss. [ 21 ] This may be due to less exposure of obese men to ultraviolet radiation, which stimulates biosynthesis of cholecalciferol (VD3) from cholesterol. [ 22 ] Indeed, the synthesis of an active metabolite of VD known as 1,25-dihydroxy VD is enhanced, and high levels showed negative feedback impact on synthesis of 25-OH VD in the liver.…”
Section: Discussionmentioning
confidence: 99%